Childcare Strategies of Single Mothers in the Face of Marketised Health Services - Frida Emilia Horta-Garduño; Ybette Karen Ramos-Gutiérrez; Itzia María Cazares Palacios (Musas)
Introduction. The price increase at the DIF Children’s Hospital, which provides public health services to the child population in the city of Pachuca, Hidalgo, Mexico, has exposed the social and economic effects on vulnerable Mexican families, such as those headed by single mothers. Objective. To find out the strategies for the health care of their children used by single mothers aged between 20 and 50 years in the city of Pachuca, Hidalgo, Mexico, following the price increase at the DIF children’s hospital. Material and methods. A qualitative methodology with semi-structured interviews was used to collect information. The chain strategy was used to contact the participants. Results. The main strategy used by the participants was the search for extra income to cover the costs of caring for their children’s health after the increase in hospital fees, in addition to the support networks, mainly family members, in their instrumental nature. On the other hand, it can be seen that facing these difficulties takes its toll on the physical and mental health of the participants. Conclusions. Mothers find it necessary to generate functional strategies to care for their children’s health, leaving aside their own physical and mental care, as it is more important for them to keep their children safe and healthy.